An exploratory examination of serious surfers: Implications for the surf tourism industry - Sotomayor, Sandra (2015)
Surf tourism is a multibillion dollar industry expected to continue expanding. Despite such economic significance, the surf tourism literature has gaps related to surf tourism segments. In response, this study applied the serious leisure framework to profile serious surfers and contrast their sociodemographic composition and travel behaviors. Although more serious surfers are more avid travelers in the quest for the perfect wave as compared with less serious surfers, preference for local attractions and conveniences did not vary between groups. In addition to contributing the scholarship of serious leisure and surf tourism, this study provides insights for the surf tourism industry. Journal: International Journal of Tourism Research 2015